Unhandled horses classified with broken/unbroken test (BUT) exhibit longer avoidance, flight reactions, and displacement behaviors when approached by humans - Riva, Maria Giorgia; Sobrero, Lucia; Menchetti, Laura; Minero, Michela; Padalino, Barbara; Dalla Costa, Emanuela (Frontiers in Veterinary Science, 2022)
Horses with a low level of tameness are at higher risk for transport-related disease and injury; hence, European regulations for the protection of animals during transport (EC 1/2005) are stricter for unhandled (unbroken) horses. However, the regulation does not provide adequate tools for unhandled horse identification. The Broken/Unbroken Test (BUT) was developed and validated to easily identify whether a horse is broken (handled) or not. As a further validation step, the aim of this study was to assess whether there is any correspondence between the BUT classification and the behavioral response of the horse. One hundred healthy Italian Heavy Draft horses were video recorded when assessed with the BUT. Ninety videos (48 handled and 42 unhandled horses) matched the inclusion criteria and were assessed. The behavior of each horse was evaluated by three blind observers with a focal animal continuous recording method. Behaviors were classified in four categories: stress, avoidance, displacement, and aggressiveness. A Mann–Whitney test was used to identify differences in behavioral patterns between horses classified as handled or unhandled with the BUT. Unhandled horses showed not only a significantly longer time to be approached by the handler, but also more avoidance and flight reactions (p < 0.001). Unhandled horses showed significantly longer displacement behaviors, such as sniffing (p < 0.001). These findings further validate the BUT classification and confirm that horses classified as unhandled are more prone to show avoidance and flight reactions when approached by humans. For this reason, the adoption of the BUT could be helpful to minimize humans’ horse-related injuries and, if applied regularly before loading, to contribute to safeguard the welfare of horses during transport.